Cyclopecten Verrill 1897 - Dijkstra, Henk H.; Beu, Alan G. (Zenodo, 2018)
Cyclopecten Verrill, 1897 Cyclopecten Verrill, 1897: 70. Type species (by subsequent designation, Sykes et al., 1898): Pecten pustulosus Verrill (1873: 14); Recent, near Georges Bank, off Newfoundland, Canada, 274 m. Xenamussium Oyama, 1944: 244 (proposed as a subgenus of Propeamussium ). Type species (by original designation): Pecten hoskynsi Forbes (1844: 146, 192); Recent, “ Asia minor ” [= off Turkey]. Diagnosis . Shell equivalve, small, circular in most species, laterally compressed, prodissoconch smooth, weakly inflated; left valve of most species sculptured with radial and/or commarginal costellae or striae, right valve with commarginal lamellae; auricles unequal; byssal notch welldeveloped; without internal radial riblets. Distribution . Paleocene?, Oligocene–Recent (Waller, 2011). Cosmopolitan, subtidal to hadal (Hayami & Kase, 1993: 59). Most representative Cyclopecten species from the Indo-West Pacific region, however, live in deep water (Habe, 1977; Bernard, 1983; HHD, unpubl. data). Discussion . Verrill (1897: 70) mentioned in his description “few pectinidial teeth [= ctenolium], byssus and byssal threads”, which are based on “ Cyclopecten ” circularis (G. B. : Published as part of Dijkstra, Henk H. & Beu, Alan G., 2018, Living Scallops of Australia and Adjacent Waters (Mollusca: Bivalvia: Pectinoidea: Propeamussiidae, Cyclochlamydidae and Pectinidae), pp. 113-330 in Records of the Australian Museum (Rec. Aust. Mus.) (Rec. Aust. Mus.) 70 (2) on page 148, DOI: 10.3853/j.2201-4349.70.2018.1670, http://zenodo.org/record/5299017 : {"references": ["Verrill, A. E. 1897. A study of the family Pectinidae, with a revision of the genera and subgenera. Transactions of the Connecticut Academy of Arts and Sciences 10: 41 - 96.", "Sykes, E. R., E. A. Smith, and G. C. Crick. 1898. The Zoological Record 34 (1897). Part 7: Mollusca. London: Zoological Society of London.", "Verrill, A. E. 1873. Results of recent dredging expeditions on the coast of New England. American Journal of Science, Series 3 5: 1 - 16, 98 - 106. https: // doi. org / 10.2475 / ajs. s 3 - 5.25.1", "Oyama, K. 1944. Classification of the genus Propeamussium. Venus 13: 240 - 254.", "Waller, T. R. 2011. Neogene paleontology of the northern Dominican Republic. 24. Propeamussiidae and Pectinidae (Mollusca: Bivalvia: Pectinoidea) of the Cibao Valley. Bulletins of American Paleontology 381: 1 - 198."]}